Previsional space during direct laryngoscopy: Implication in the difficult laryngoscopy - Park, Seongjoo (Medicine (Baltimore), 2017)
The laryngoscope should displace oral soft tissues forward out of the operator's vision. Therefore, the space in front of the view may be critical for determining the laryngoscopic view. The aim was to investigate the difference in the previsional space during difficult versus easy laryngoscopy (EL). Under general anesthesia, digital photographs of the lateral view of the head and neck were taken in the horizontal sniffing position, after head extension, and during laryngoscopy with a defined force (50 N). Three points (thyroid notch (T), maxillary incisor (I), and mandibular mentum (M)) were marked on the photograph. The previsional space was defined as the TIM triangle. We compared these areas and other variables of the TIM triangle between male patients with difficult laryngoscopy (DL: Cormack–Lehane III–IV, n = 12) versus those of age- and body mass index-matched male patients with EL (Cormack–Lehane I–II, n = 12). When the head was extended, the areas TIM triangle in DL were significantly smaller than in EL. During laryngoscopy, all values of the TIM triangle in DL, including the TIM area (16.4 ± 3.7 vs 22.6 ± 2.8 cm(2), P < .01), were significantly smaller than the values in EL. The previsional space was smaller in patients with DL than in those with EL. The TIM triangle could suggest new way to explain the mechanism underlying DL.